PENGARUH STRATEGI PEMBELAJARAN INQUIRY LEARNING TERHADAP HASIL BELAJAR PAI SISWA KELAS VIII DI SMPN 02 PURWOSARI - Achmat Mubarok; Lili Maslukha (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
This thesis discusses the "influence of inquiry learning strategies in PAI lessons on student learning outcomes at SMPN 02 Purwosari. subproblem 1. How is the application of inquiry learning strategy in PAI lessons at SMPN 02 Purwosari? 2.Is there any effect of inquiry learning strategy on PAI learning outcomes for SMPN 02 Purwosari students?. In addition, the purpose of this study was to describe the effect of inquiry learning strategies on PAI learning outcomes for class VIII C students of SMPN 02 Purwosari. The approach used is a quantitative approach using statistical analysis. the type of research used is Ex Post Facto. The population in this study were all students of SMPN 02 Purwosari, totaling 213 students. The sample taken is class VIII C, which consists of 32 students. The technique used is purposive sampling technique. The research instrument used a questionnaire and documentation. The collected data was processed using descriptive statistical analysis and inferential analysis with simple regression techniques. The results of descriptive statistical analysis of the average score of variable X regarding the application of inquiry learning strategies in PAI learning are 79 very high categories because they are in the interval (78-83). This means that the application of inquiry learning strategies in PAI learning is included in very high qualifications. The results of descriptive statistical analysis obtained the average score (mean) of the Y variable regarding PAI learning outcomes for students at SMPN 02 Purwosari is 82 with a very high category because it is in the interval (82-89). This means that the average PAI learning outcomes of SMPN 02 Purwosari students are included in very high qualifications.